A short note on a 3D spectral analysis for turbulent flows on unstructured meshes - Tsoutsanis, Panagiotis; Nogueira, Xesús; Fu, Lin (Elsevier, 2022)
We propose two techniques for computing the energy spectra for 3D unstructured meshes that are consistent across different element types. These techniques can be particularly useful when assessing the dissipation characteristics and the suitability of several popular non-linear high-order methods for implicit large-eddy simulations (iLES). Numerical experiments demonstrate the performance of several element types for iLES of the Taylor-Green vortex, where a significantly different dissipation and dispersion mechanism for each element type is revealed. The energy spectra results are dependent on the technique selected for obtaining them, therefore an additional established technique from the literature is also included for comparison to further analyse their similarities and their differences. These techniques can be an integral tool for the tuning and calibration of non-linear high-order methods that can benefit both explicit and implicit large-eddy simulations (LES).
Keywords: FFT; Unstructured Meshes; Implicit large eddy simulation; Turbulent flow; High-Order Non-Linear Methods